Evaluation Prototype of B30 Diesel Fuel Heater Using Arduino - Parabelem Tino Dolf Rompas; Metsi Daud; Ahmad Tubagus Tsani Risqi Aji; Barokah; Dwi Dharma Arta Kusuma; Ahmad Ilham Ramadhani (International Journal of Marine Engineering Innovation and Research, 2024)
Utilizing B30 as diesel fuel has the advantage of being heated to a specific temperature. Manually setting the temperature during the heating and fuel-filling process in the heating tank causes fuel performance to become less effective and efficient. This research aims to evaluate the capability of the prototype as a B30 fuel heater. The research method was carried out experimentally by testing variables for the temperature sensor (DS28B20), distance sensor (VL53LOX), heater control system, fuel filling system, and performance of the B30 diesel fuel heater prototype on a 7 HP single-cylinder diesel engine. The research results show that the fuel heater prototype can regulate the desired temperature and fill the heating tank automatically. The fuel temperature tested starts from 280C to 650C with an average multiple of 50C and tolerances of +20C and -10C. At the same time, it can automatically fill fuel from the main tank to the heating tank set from 800 ml to 1200 ml. B30 performance on a 7 HP single-cylinder diesel engine with 100 ml of fuel heated at 280C - 650C each shows the longest fuel consumption time at 350C and the fastest at 450C.